SECTORAL POLICIES IN THE POST-COVID-19 PERIOD - Emilia STOICA; Liviu RADU (Challenges of the Knowledge Society)
National economies, but also the global economy as a whole, face major challenges caused primarily by the effects of the corona pandemic, to which are added factors that stimulate destabilizing trends in the value chain in the international economy: a new industrial revolution in the digital age; accentuation of nationalism and, implicitly, of protectionism; the urgent need to protect the natural environment, etc. In a such unstable economic and social situation, the policies and programs developed and implemented by public authorities are crucial both for economic development and for improving the quality of life. Public interventions of any kind: in the field of public finances; monetary policy; those aimed at investments; technical and technological progress, etc. will have to consider, on the one hand, the increase of the added value in the productive sectors of the national economy that present comparative advantage and, on the other hand, given equally important, to ensure the material, human, capital resources for this development, simultaneously with the appropriate satisfaction of life needs - food, health, education, services, etc. - of the population. In this sense, the institutional sectoral structure of the national economy has always been, but especially in the present period, a major importance for policy makers, and sectoral prioritization in public policy interventions is a constant concern of the utmost importance for economic and social resilience of any country.